(3cJGH aj GdWHs ((3EScfOQ Hf eSYO Hf YHOGdfHj s)
(3ChdgG (B:s
(3hjfOQ ajg hjMbf, hfhY ef gPg GdYdI jSei GdTNhU , hHSHHI eGOI ShOGhjI ZdjXI JHNQ Edi GdOeGZ s
(3BNQgG (B:s
(3UaI Mdh ddMdb hef dHGH GdNHR GdeaJhJ HGdjO GdefNhd bOQ GdcajI, hjMQc JMQjckG LjOkG HGddhR hGdaSJb GdebTQjf hGddg CYde s
(3HgG UaMGJ cKjQI egRhRIs
(3hcPdc HgG NQe Hjf GdHGH (B13 (3h (B19 (3ef GdebGdI GdKGfjIs
(3hGdHGH (B37 (3h (B49 (3ef GdebGdI GdKGdKIs
(3TGQc GdfGSN aj fSN GdeNWhW eSGYO Hf MeRI Hf fUQ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdWHs